10.000 DWT Coal Vessel/Barge Open Pier Jetty Planning at Molotabu, Gorontalo - Zain, Farel Aimar; Fuddoly, Fuddoly; Buana, Cahya (Jurnal Teknik ITS, 2024)
Coal exports and imports are common in Indonesia, especially Gorontalo, North Sulawesi, which is always involved in coal export and import activities. Coal is one of the important energy sources in this country. These activities always involve ships. A ship certainly needs a station like any other form of transportation. Open pier construction has various regulations so that vessel can dock safely. Various things can affect the dimension and even the strength of the port structure. From the planning of the pier, implementation methods are also carried out to calculate the planned cost budget The results of planning an open pier jetty for a 10,000 DWT barge include a minimum depth recommendation of -6.5 mLWS. Recommended jetty dimensions are 108 m long and 20 m wide at an elevation of +2.5 mLWS. From the results of the upper structure calculations, a plate with a thickness of 35 cm was obtained. Then for the beam requirements for the jetty structure (500 x 750 mm) and fender beams (2600 x 2500 x 1200 mm). For single pile cap required (2000 x 2000 x 1000 mm) and batter pile cap (3000 x 2000 x 1000 mm). From the results of the substructure calculations, it was found that D609 mm steel piles with a thickness of 12 mm were needed for the jetty structure. Dredged volume requirement is 20,300 m3. Breast wall dimensions (400 x 2000 mm), cantilever dimensions (150 x 250 mm), foot dimensions (2500 x 400 mm), and stiffener thickness of 30 cm. From the overall calculation results, the implementation method can be planned as follows. Preparatory work, dredging work, retaining wall work, jetty structure work, and fender and bollard installation work. From this work, the total cost required is Rp. 51.324.256.809.k, the total cost required is Rp. 51.324.256.809